Les espaces chinois de Kolkata : simples marges convoitées dans une grande ville indienne ou support des influences singapouriennes et chinoises ? - Catherine Guéguen (EchoGéo)
The Kolkata Chinese community has an uncommon profile compared to the other overseas Chinese communities: its population is decreasing (fewer than 5000 members nowadays). Its spaces, which were economically prosperous up to the 1960s, are now undergoing changes which are partially controlled by the community. The reconversion of the tanneries district into a restaurant zone is not likely to prove durable, as it is coveted by estate companies who argue in favor of heritage preservation. Those Chinese districts also reveal other stakes: some are diplomatic and concern Mainland China, others illustrate the spread of Chinese districts inspired by Singapore. The spaces occupied by the Kolkata Chinese community may look abandoned to the average visitor, but they bring out new challenges that go beyond the local scale: the stake of a possible presence in India for Mainland China, the diffusion of a development model associated to Singapore’s modernity for the Kolkata municipal authorities.